(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the historical and religious foundations of attitudes toward plants in the world’s major religions. The study explores the place of plants within ancient mythologies and religious traditions across different civilizations. Trees, flowers, and fruits are shown to have been regarded as sacred symbols of life, fertility, purity, and immortality in numerous cultures. A comparative analysis is conducted of perspectives on plants in Judaism, Christianity, Hinduism, Buddhism, and Islam. Particular attention is devoted to the plants mentioned in the Qur’an, including the olive, fig, date palm, grapevine, pomegranate, sidr tree, basil, and ginger; their spiritual symbolism and practical significance are examined in detail. The article highlights the role of plants as sources of nourishment and healing within Islamic teachings, and investigates the development of ’ilm al-nabat (the science of plants) in the Muslim intellectual tradition and its relationship with botany, medicine, pharmacology, and agriculture. The study also discusses the contribution of religious beliefs to biodiversity conservation and environmental sustainability, analyzing ethnobotanical knowledge preserved through religious practices as an important source for scientific advancement. The findings indicate that religious traditions have made significant contributions to the development of botany, pharmacology, ecology, and environmental ethics, and that the relationship between religion and nature remains an important foundation for promoting ecological awareness and sustainable development in contemporary society.